Od Bacona do Hume’a – istota i odcienie empiryzmu w nowożytnej Anglii - Andrzejewski, Bolesław (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The aim of the article is to give a brief overview of English empiricism, particularly in modern philosophy. The paper will firstly examine the pre-enlightenment thought of F. Bacon, upon which it will discuss the empiricism of J. Locke, G. Berkeley and D. Hume. The general conclusion of the paper has it that although empiricism has assumed different shades, it has always permeated English culture.